An integrated electrochromic supercapacitor based on nanostructured Er-containing titania using an Er(iii)-doped polyoxotitanate cage. Issue 9 (18th July 2016) - Lv, Yaokang; Du, Weishi; Ren, Yan; Cai, Zhiwei; Yu, Kuai; Zhang, Cheng; Chen, Zuofeng; Wright, Dominic S.
Abstract : An integrated bifunctional EC supercapacitor was designed based on nanostructured Er-containing titania due to its EC properties and Li + ion storage capacity. This new material is derived from a novel Er(iii )-doped polyoxotitanate cage [Ti8 O7 (OEt)21 Er]. Abstract : The novel heterometallic polyoxotitanate cage [Ti 8 O 7 (OEt) 21 Er ] can be used as a single-source precursor for the formation of nanostructured Er-containing titania materials (Er@TiO2 ). Based on the electrochromic properties and lithium ion storage capacity of Er@TiO2, an integrated bifunctional EC supercapacitor has been designed.